2022
DOI: 10.22365/jpsych.2022.073
|View full text |Cite
|
Sign up to set email alerts
|

Dietary interventions for autism spectrum disorder: An updated systematic review of human studies

Abstract: Autism is a complex spectrum of disorders (ASD) with genetic, epigenetic, autoimmune, oxidative stress, and environmental aetiologies. Treatment of ASD using dietary approaches is a promising strategy, especially owing to its safety and availability. Our study critically analysed the roles and efficacy of antioxidants, probiotics, prebiotics, camel milk and vitamin D. This systematic review provides an updated synopsis of human studies that investigated therapeutic benefits of these dietary interventions in au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…The impact of prebiotic, probiotic, and synbiotic supplementation on Bifidobacterium in the gut was inconsistent. Some studies (Yang et al, 2020; Mitchell and Davies, 2021; Prosperi et al, 2022) reported an increase in Bifidobacterium levels, while others reported decreased levels (Lasheras et al, 2021; Amadi et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of prebiotic, probiotic, and synbiotic supplementation on Bifidobacterium in the gut was inconsistent. Some studies (Yang et al, 2020; Mitchell and Davies, 2021; Prosperi et al, 2022) reported an increase in Bifidobacterium levels, while others reported decreased levels (Lasheras et al, 2021; Amadi et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The ketogenic diet also has effects on epigenetic mechanisms 56 . The gut metabolites of some phytoestrogens can act as epigenetic modulators for improved human health 57 . An improved behavioral symptoms was observed by both vitamin D initiated by antioxidants and polyphenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…56 The gut metabolites of some phytoestrogens can act as epigenetic modulators for improved human health. 57 An improved behavioral symptoms was observed by both vitamin D initiated by antioxidants and polyphenolic compounds. While decreased inflammatory cytokines were seen with the latter, neurotoxicity was conferred against the former.…”
Section: Factors Influencing Both Epigenetics and Gmmentioning
confidence: 98%
“…The effect of vitamin D on the intestinal microflora was also confirmed in a pilot clinical study by Charoenngam et al Similar to Singh, they investigated the gut microbiome following an intervention with oral vitamin D (600, 4000 and 10,000 IU/day) in adults deficient in vitamin D. They observed a dose-dependent reduction in inflammatory bowel disease associated with an increase in commensal bacteria while reducing the amount of pathogens [107]. Altering the diversity of the gut microflora with vitamin D supplementation has also been studied in many diseases, including cystic fibrosis [108], multiple sclerosis [109], autism/autism spectrum disorder [110,111], diabetes, and obesity [112]. Kanhere et al assessed the effect of a 12-week intervention with high doses of vitamin D (50,000 IU/week) on the composition of the intestinal and respiratory microflora in patients with cystic fibrosis with vitamin D deficiency.…”
Section: Gut-brain Axismentioning
confidence: 99%
“…Similar findings were presented by Cantarel et al, who assessed vitamin D supplementation (5000 IU/day for 90 days) on the intestinal microflora in multiple sclerosis. They also noted a shift in the composition of the intestinal microflora in favor of commensal bacteria [110]. Finally, Hussein et al investigated the effect of vitamin D (500 IU/kg/day) on the colon cannabinoid 1 receptor (CB1R), which directly connects the gut microflora to metabolic and cognitive disorders, compared to metformin (200 mg/kg/day) in rats.…”
Section: Gut-brain Axismentioning
confidence: 99%